A HAMILTON-JACOBI TREATMENT OF DISSIPATIVE SYSTEMS - Jarab’ah, Ola A.; Nawafleh, Khaled I.; Ghassib, Humam B. (European Scientific Journal, ESJ, 2013)
Dissipative systems are investigated within the framework of the Hamilton-Jacobi equation. The principal function is determined using the method of separation of variables. The equation of motion can then be readily obtained. Three examples are given to illustrate our formalism: the damped harmonic oscillator, a system with a variable mass, and a charged particle in a magnetic field.